Union Rates of Talar Neck Fractures With Substantial Bone Defects Treated With Autograft. (March 2022) - McMurtrie, J. Thompson; Patch, David A.; Frazier, Mason B.; Wills, Bradley W.; Prather, John C.; Viner, Gean C.; Hill, Margie J.; Johnson, Michael D.
Background: This study evaluated the union rate of talar neck fractures with substantial bone defects treated acutely with autologous tibial bone graft during primary osteosynthesis. Methods: A case series at a level 1 trauma center was performed to identify consecutive patients who underwent operative fixation of talar neck fracture with autograft ( Current Procedural Terminology codes 28445 and 20902) between 2015 and 2018. "Substantial bone defect" was defined as a gap greater than 5 mm in the sagittal plane and greater than one-third of width of the talar neck in the coronal plane. Postoperative foot computed tomographic (CT) scans were obtained for all patients. Primary outcome was union, and secondary outcomes were malunion, avascular necrosis (AVN), post-traumatic arthritis (PTA), and patient-reported outcomes (PROs). Results: Twelve patients with 12 fractures were included in the series, with an average length of follow-up of 26 months (range: 7-55) The average age was 34 years (17-59), and the most common mechanism of injury was motor vehicle crash. The Hawkins classification of the fractures was 4 type II (2 type IIA and 2 type IIB) (33%) and 8 type III (67%). Four fractures (33%) were open fractures. Union was achieved in 11 patients (92%). There was 1 malunion (8%). AVN was identified on postoperative CT scans in 11 patients (92%). Three of these 11 eventually showed collapse. Ten patients (83%) had radiographic evidence of some degree of ankle PTA, and 12 patients (100%) had radiographic evidence of some degree of subtalar PTA. Average Patient-Reported Outcomes Measurement Information System–Short Form score was 37 (32-45) and average Foot and Ankle Ability Measure activities of daily living and sports subscale scores were, respectively, 61 (31-87) and 31 (0-71), respectively. Average visual analog scale score was 5 (0-10), and average Foot Function Index was 49 (7-89). SF-36 scores showed fair to poor outcomes in the majority of patients. Conclusion: In this relatively small series, tibial autograft in primary osteosynthesis of comminuted talar neck fractures with substantial bone defects is associated with excellent union rates and low malunion rates. Despite high union rates, secondary outcomes of AVN with or without collapse, ankle and subtalar PTA, and relatively low PROs were common. Level of Evidence: Level IV, case series.